DENTAL AND ORAL HEALTH OF ELEMENTARY STUDENTS DURING THE PANDEMIC OF COVID-19 - Martha Mozartha; Siti Rusdiana Puspa Dewi; Ulfa Yasmin; Hema Awalia; Sulistiawati Sulistiawati (Fakultas Kedokteran Universitas Sriwijaya, 2021)
The Covid-19 cases have caused limited access to dental and oral health services and education, especially for school children who have higher caries risk. Factors affecting children's dental and oral health during the pandemic need to be studied, and special attention regarding caries prevention measures at this time is needed to be discussed. The purpose of this literature review article is to discuss the dental and oral health of elementary school-age children during the Covid-19 pandemic.